Elderly ovarian cancer patients: An individual participant data meta-analysis of the North-Eastern German Society of Gynecological Oncology (NOGGO). (June 2016) - Woopen, H.; Inci, G.; Richter, R.; Chekerov, R.; Ismaeel, F.; Sehouli, J.
Abstract: Background: Barriers for optimal treatment and enrolment in clinical trials are the physicians' perceptions towards age, comorbidities and fear of toxicity as well as the eligibility criteria of clinical trials. There is a high need to gain more knowledge about this patient group in order to optimize treatment. We aimed to evaluate the influence of age above 65 years on comorbidities, comedication, grade III/IV toxicity, prior discontinuation of chemotherapy and survival. Patients and methods: An individual participant data meta-analysis of three phase II/III studies ('Tower', 'Topotecan phase III' and 'Hector') of the North-Eastern German Society of Gynecological Oncology including 1213 patients with recurrent ovarian cancer was conducted using logistic regression and Cox regression analysis. Results: Median age at diagnosis was 59 years. The patient group ≥65 years included 349 versus 864 patients younger than 65 years. Cardiovascular disease and diabetes were more frequent in the older age group (p < 0.001 and p = 0.001). Haematological and cardiovascular grade III/IV toxicities were more often seen in patients above 65 years, while non-haematological toxicity was not (p = 0.03, odds ratio [OR] 1.35; p = 0.04, OR 1.83; and p = 0.90, OR 0.98, respectively). There was no difference in prior discontinuation of treatment in multivariate analysis. Cox regression showed a trend towards poorer progression-free survival (p = 0.053, hazard ratio 1.143) in the older age group. Conclusion: Haematological and cardiovascular toxicities are more frequent in elderly patients. However, this did not influence prior discontinuation of therapy. Elderly patients should not be deprived of adequate chemotherapy or excluded from clinical studies just because of their age. Thorough geriatric assessment and monitoring is mandatory. Highlights: Cardiovascular disease and diabetes are more frequent in the elderly. There was no difference between both age groups concerning polypharmacy. Haematological toxicity was more frequent in the elderly, while chemotherapy was not discontinued earlier than planned.